Photoconductive UV Detectors Based on ZnO Films Prepared by R.F. Magnetron Sputtering Method - Tuyen, Nguyen Viet; Canh, Ta Dinh; Long, Nguyen Ngoc (Communications in Physics, 2012)
Highly c-axis oriented zinc oxide (ZnO) thin films were deposited on glass substrates by radio frequency (r.f.) sputtering. The photoconductor UV detector based on ZnO films, having a metal-semiconductor-metal (MSM) structure with interdigitation configuration, were fabricated by using aluminium (Al) as a contact metal. The characteristics of dark and photocurrent of the ultraviolet (UV) detector and the UV photo-response of the detector were investigated. The linear current-voltage (I-V) characteristics under both forward and reverse bias exhibit ohmic metal-semiconductor contacts. Under illumination by monochromatic light at a wavelength of 365 nm, the photo-generated current was measured to be 0.56 μA at a bias of 6 V. The photo-response decay in these devices is slow.